2022
DOI: 10.1371/journal.pone.0262882
|View full text |Cite
|
Sign up to set email alerts
|

Access to HIV care in jails: Perspectives from people living with HIV in North Carolina

Abstract: Most incarcerations for people living with HIV (PLWH) occur in jails, yet studies of HIV care during jail incarceration are limited. As part of a larger study to explore the ethical considerations in extending public health HIV surveillance to jail settings, we conducted semi-structured interviews with twenty-three PLWH with more than 300 distinct jail incarcerations post HIV diagnosis in 21 unique North Carolina jails. Interviews included questions about HIV disclosure in jail, the type of HIV care received i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, prisoners should have the human right to access at least the same level of tuberculosis care as that offered in their communities Alemayehu et al [ 21 ] Ethiopia Cross-sectional study Mental health and bioethics in prisons An incidence of depression was found among prisoners, especially among those with poor general health, long years of imprisonment and worries about children were the most vulnerable. It is absolutely necessary to strengthen mental health services in prisons Blue et al [ 22 ] North Carolina Survey HIV treatment/prevention and bioethics in prisons The analysis highlighted a worsening of access to HIV treatment in prison, a negative impact of prison detention on the continuity of HIV treatment, a reduction in privacy and stigmatization. More outside resources are needed, such as from state and local health departments, so that prisons can promptly provide HIV medications to people with disabilities incarcerated in their facilities Green et al [ 23 ] Ontario Survey Access to care in prison and bioethics in prisons Usually, people entering prison have a need to access primary care, as in most cases they have unmet health needs.…”
Section: Resultsmentioning
confidence: 99%
“…However, prisoners should have the human right to access at least the same level of tuberculosis care as that offered in their communities Alemayehu et al [ 21 ] Ethiopia Cross-sectional study Mental health and bioethics in prisons An incidence of depression was found among prisoners, especially among those with poor general health, long years of imprisonment and worries about children were the most vulnerable. It is absolutely necessary to strengthen mental health services in prisons Blue et al [ 22 ] North Carolina Survey HIV treatment/prevention and bioethics in prisons The analysis highlighted a worsening of access to HIV treatment in prison, a negative impact of prison detention on the continuity of HIV treatment, a reduction in privacy and stigmatization. More outside resources are needed, such as from state and local health departments, so that prisons can promptly provide HIV medications to people with disabilities incarcerated in their facilities Green et al [ 23 ] Ontario Survey Access to care in prison and bioethics in prisons Usually, people entering prison have a need to access primary care, as in most cases they have unmet health needs.…”
Section: Resultsmentioning
confidence: 99%
“…4 Again, female prisoners had disproportionately less access to antiretroviral therapy. 19,23 A recent study by Blue et al 41 reported that, in North Carolina, apart from the issue of access to medicines while incarcerated, the availability of ARVs was further impacted by inadequate prison resources. The limited health and human resource capacity in African settings has been well elucidated, and such challenges within prison settings pose a significant risk to the adequacy of care received by inmates, as was reported in some of the studies reviewed.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Other populations that may be affected by treatment interruptions could include PLWH who are detained either short-term or long-term in a jail or prison setting, or residing in a skilled nursing facility or long-term care facility. 32 These patients will require additional coordination by healthcare team to transport patient to and from injection appointments, if possible. In addition, patients should also be aware of how long a visit will take.…”
Section: Clinical Considerationsmentioning
confidence: 99%